2021
DOI: 10.1192/bja.2021.64
|View full text |Cite
|
Sign up to set email alerts
|

How is the COVID-19 pandemic affecting women's menstrual cycles and quality of life? A view from South Asia

Abstract: SUMMARY The substantial strain that women are facing during the COVID-19 pandemic can affect their menstrual cycle and further impair their quality of life. In low- and middle-income countries, this strain is exacerbated by: cultural taboos and poor education related to menstruation; ‘period poverty’; unavailability of menstrual hygiene products; and poor hygiene facilities. We suggest actions that governments, healthcare professionals and individuals can take to address these factors and minimise the psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The COVID-19 pandemic caused the prevalence of depression, stress, and anxiety among women in general. Many studies reported shorter or longer menstrual cycles and irregular menstrual volume because of psychological pressure in pandemics (18)(19)(20)(21) and COVID-19 vaccination (22,23)…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic caused the prevalence of depression, stress, and anxiety among women in general. Many studies reported shorter or longer menstrual cycles and irregular menstrual volume because of psychological pressure in pandemics (18)(19)(20)(21) and COVID-19 vaccination (22,23)…”
Section: Resultsmentioning
confidence: 99%
“…These effects were found to be consistent across countries. In addition, Hashmi et al (2022) emphasize that their findings highlight the universal protective role of compassion, particularly self-compassion and compassion from others, in promoting resilience by buffering against the COVID-19 pandemic's negative effects on mental health and social safety. Furthermore, the aforementioned study shows that compassion fears amplify the negative impact of the COVID-19 pandemic on mental health and social safety.…”
Section: Theoretical Contributionmentioning
confidence: 97%
“…Nonetheless, the execution of public health policies also faces challenges that necessitate adapting to specific environments and catering to varying populations' needs, especially marginalized communities, including impoverished individuals, refugees, and rural residents (Alugnoa et al, 2022). External factors, such as economic crises and public health events like the COVID-19 pandemic, may also exert an influence on menstrual poverty (Hashmi et al, 2022;Sommer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%